Modeling the effect of bilateral sagittal split osteotomy on posterior, superior and medial space dimensions of the temporomandibular joint: a retrospective controlled cohort study - Linus Christian Hupp; Michael Verius; Annika Bertram; Andreas Kolk; Rüdiger Emshoff (BMC, 2023)
Abstract Background To model the effect of isolated bilateral sagittal split osteotomy (BSSO) on changes in posterior (PSD), superior (SSD), and medial space dimensions (MSD) of the temporomandibular joint. Methods Using a retrospective cohort study design, pre- and postoperative (immediately after surgery; 1 year follow-up) cone-beam computed tomography measurements of 36 patients who had undergone BSSO for mandibular advancement were compared with a control group of 25 subjects from whom a mandibular odontogenic cyst was removed under general anesthesia. Generalized estimation equation (GEE) models were used to examine the independent effects of study group, preoperative condylar position, and time points on PSD, SSD, and MSD adjusting for covariates (age, sex, and mandibular advancement). Results No significant differences were found regarding changes in PSD (p = 0.144), SSD (p = 0.607), or MSD (p = 0.565) between the BSSO and control groups. However, the preoperative posterior condylar position showed significant effects on PSD (p < 0.001) and MSD (p = 0.043), while the preoperative central condylar position demonstrated a significant effect on PSD (p < 0.001). Conclusion The data suggest that preoperative posterior condylar position is a significant effect modifier of PSD and MSD over time in this cohort.